2018
DOI: 10.1051/0004-6361/201732342
|View full text |Cite
|
Sign up to set email alerts
|

Average fractional polarization of extragalactic sources at Planck frequencies

Abstract: Recent detailed simulations have shown that an insufficiently accurate characterization of the contamination of unresolved polarized extragalactic sources can seriously bias measurements of the primordial cosmic microwave background (CMB) power spectrum if the tensor-to-scalar ratio r ∼ 0.001, as predicted by models currently of special interest (e.g., Starobinsky's R 2 and Higgs inflation). This has motivated a reanalysis of the median polarization fraction of extragalactic sources (radio-loud AGNs and dusty … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…These results are consistent with the conclusion by Bonavera et al [127] who applied stacking techniques to radio sources detected by Planck in total intensity, finding an average fractional polarization of 3%, essentially independent of frequency from 30 to 353 GHz. A similar conclusion was reached by the independent analysis of Trombetti et al [128].…”
Section: Detecting Sources In Polarizationsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are consistent with the conclusion by Bonavera et al [127] who applied stacking techniques to radio sources detected by Planck in total intensity, finding an average fractional polarization of 3%, essentially independent of frequency from 30 to 353 GHz. A similar conclusion was reached by the independent analysis of Trombetti et al [128].…”
Section: Detecting Sources In Polarizationsupporting
confidence: 81%
“…These low values of Π are understood as due to the complex structure of galactic magnetic fields, with reversals along the line of sight, and to the disordered alignment of dust grains; both effects work to decrease the global polarization degree. Nevertheless, the current limits on the distribution of polarization fractions of dusty galaxies permit a contamination of CMB polarization maps comparable to that of radio sources down to 100-140 GHz, and dominant at higher frequencies [131,128]. The amplitude of the power spectrum of polarized dusty galaxies may be close to the level of CMB lensing B-modes and of primordial B-modes for r 0.01.…”
Section: Detecting Sources In Polarizationmentioning
confidence: 91%
“…The results shown in Table 1 are consistent with previous studies of AGN and DSFGs. Briefly, in previous studies, polarisation fraction is found to be independent of flux (Battye et al 2011;Trombetti et al 2018;Datta et al 2018) and frequency (Battye et al 2011;Galluzzi et al 2017 Weighted Mean 6 − 1500 686 6.9 ± 1.1 2.63 ± 0.22 Table 1. Mean-squared polarisation fractions ( p 2 ) and inferred fractional polarisation ( p 2 ) measurements for Nsource number of SPT-SZ selected sources stacked in flux bins Srange using 95 and 150 GHz SPTpol maps.…”
Section: Comparison To Previous Resultsmentioning
confidence: 89%
“…GHz frequencies, and overall mean p is estimated at a level around 1 − 5 per cent, which are all consistent with our findings in this work. For comparison, we show the squared values of polarisation fraction p 2 from Bonavera et al (2017a) and Trombetti et al (2018) (at 100 and 143 GHz Planck frequencies) in both panels of Fig 3. In the right panel, we also show p 2 measured by Datta et al (2018) at 148 GHz ACTpol observing frequency. On the dusty side, Bonavera et al (2017b) used Planck data to study ∼ 4700 dusty sources selected at 857 GHz with S ≥ 791 mJy (a flux threshold that is comparable to this work when extrapolated to 150 GHz).…”
Section: Comparison To Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation